The effect of social support on learning engagement among Chinese nursing interns: the mediating role of self-efficacy - Liping Wu; Yan Chen; Meiqin Xue; Weiyi Zhu; Wei Wang (BMC Nursing)
Abstract Objective While perceived social support is recognized as crucial for nursing interns’ development, its psychological pathways influencing learning engagement remain unclear. This study focuses on the relationships among perceived social support, self-efficacy and learning engagement of nursing interns, as well as the mediating role of self-efficacy. Methods A cross-sectional study design was adopted. A total of 309 nursing students interning at a tertiary Grade A hospital in Shanghai were recruited via convenience sampling. These students were enrolled in 12 different universities in Shanghai. The Perceived Social Support Scale, General Self-Efficacy Scale, and Utrecht Work Engagement Scale-student were used to measure perceived social support, self-efficacy, and learning engagement among the nursing interns.SPSS 21.0 was employed to explore variable relationships, and AMOS 26.0 was utilized for mediation analysis. Results There were significant positive correlations among the perceived social support (69.04 ± 11.15), self-efficacy (27.78 ± 6.63), and learning engagement (84.42 ± 21.24) of nursing interns (p = 0.000). Perceived social support of nursing interns positively predicted learning engagement (β = 0.279, p = 0.000). In the two pathways of perceived social support (β = 0.501, p = 0.000) and learning engagement (β = 0.469, p = 0.000), the regression coefficient of self-efficacy was significant. The mediating effect accounted for 45.72% of the total effect. Notably, only-child nursing interns exhibited higher self-efficacy (t = 2.372, p = 0.018). Conclusion Perceived social support significantly enhances the learning engagement of nursing interns through the mediating effect of self-efficacy. Educators should strengthen the social support system and focus on cultivating nursing interns’ self-efficacy, particularly for non-only-child nursing interns, to optimize learning outcomes. These findings offer actionable insights for developing nursing education strategies.